2022
DOI: 10.3390/universe8020126
|View full text |Cite
|
Sign up to set email alerts
|

Palatini f(R) Gravity and Variants of k-/Constant Roll/Warm Inflation within Variation of Strong Coupling Scenario

Abstract: We show that upon applying Palatini f(R), characterized by an αR2 term, within a scenario motivated by a temporal variation of strong coupling constant, then one obtains a quadratic kinetic energy. We do not drop this term, but rather study two extreme cases: α<<1 and α>>1. In both cases, one can generate a kinematically-induced inflationary paradigm. In order to fit the Planck 2018 data, the α>>1 case, called k-inflation, requires a fine tuning adjustment with nonvanishing nonminimal couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…the theoretical results of different cases and limitations are compared to the joint 68 and 95% CL regions for n s , and r, obtained from Planck 2018 and lensing data alone, and their combinations with BICEP2/Keck Array (BK15) and BAO data, in addition to a forecast posterior contours of the CMB experiments (Simons Observatory, CMB-S4, and LiteBIRD)considered in [14].NI, ExP, and NS stand for Natural inflation, Exponential Potential, and New Scan, respectively. In figure (1), we reproduce most of the results of [5] and [6] regarding the cases of table (2). The exemplified results of figure (1) were largely in agreement with the observations of Planck2018 [5], [6].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…the theoretical results of different cases and limitations are compared to the joint 68 and 95% CL regions for n s , and r, obtained from Planck 2018 and lensing data alone, and their combinations with BICEP2/Keck Array (BK15) and BAO data, in addition to a forecast posterior contours of the CMB experiments (Simons Observatory, CMB-S4, and LiteBIRD)considered in [14].NI, ExP, and NS stand for Natural inflation, Exponential Potential, and New Scan, respectively. In figure (1), we reproduce most of the results of [5] and [6] regarding the cases of table (2). The exemplified results of figure (1) were largely in agreement with the observations of Planck2018 [5], [6].…”
Section: Resultssupporting
confidence: 84%
“…In figure (1), we reproduce most of the results of [5] and [6] regarding the cases of table (2). The exemplified results of figure (1) were largely in agreement with the observations of Planck2018 [5], [6]. We see, however, that the opposite occurs when Planck 2018 and lensing data alone and their combinations with BICEP2/Keck Array (BK15) and BAO data are taken into account.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In [78], we studied the effect of both NMC to gravity and an extended αR 2 gravity applied to an inflationry model inspired by "variation of constants" leading to an exponential potential of a certain form, and found that the joint effects of both factors allowed an accommodation with data. On the other side, we apply the same techniques in this work on the NI and see that both effects allow a sort of "focusing" of the predictions, so that increasing "α" pushes the predictions downward towards smaller r whereas increasing the NMC parameter "ξ" pushes the predictions rightward towards larger n s , and that both factors play in a disjoint way of each other, in such a way that one can meet the observational constraints, even if they were tight.…”
Section: Jcap10(2022)001mentioning
confidence: 99%
“…Strictly speaking, we are assuming also the potential V(φ) to be negligible. This assumption can be supported in relation to the inflation theory, for which during the Planck era the inflation field ( [3,37]) is a non-interacting field (for an alternative paradigm about the power-law inflation in the f (R) gravity see [38,39]). The conditions under which the potential of the f (R) theory is negligible will be discussed later.…”
Section: Kasner-like Solutions In F (R)-gravitymentioning
confidence: 98%